The phenomenon of electronic extortion and prevention methods Sociological reading and theoretical opinions - - ZIUOCHE, Said (Social Sciences Journal)
Cyberextortion are relatively new phenomena where she didn’t appear until the emergence and expansion of the Internet, and with the advent of communication became increasingly famous phenomenon affecting Algerian society without exception classes, this phenomenon has taken several dimensions, where the most important occurrence of theft and rapes, and we said that all social institutions the tasks assigned to them under the protection and prevention of risk of Cyberextortion in full coordination with the various security devices that never slackened in surveillance, research and investigation From these criminals, while remaining methods of prevention from falling victim to the racketeer of major foundations that one must follow to ensure protection and security